Men's squash team (Tufts Archival Research Center, 2015)
photographic print. Back row (left to right): Steve Filosa, Peter Pagnucco, Brian Golden, Drew Cohen, James Ellman, Mark Elman, Head Coach Bill Summers Front row (left to right): Toby Ali, Mark Anstendig, Chris Waldorf, Captain Dan Horan, Josh Lebowitz, Jim Porter, Andy Obermeier